MORAL DEVELOPMENT THROUGH STUDENT PROSELYTIZING ORGANIZATION - Yanti Amalia Afifah; Nopri Dwi Siswanto (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2023)
Moral development plays an important role to be implemented among the University students because they will be the next generation to build this nation. One of the way to develop their moral is asking them to join Islamic organization, such as organization of Student Da'wah Institution in the University. The focus of this research is to investigate the moral development through the organization of Student Da 'wah Institutions in Sunan Gunung Djati State Islamic University Bandung. The approach of this research was qualitatively with descriptive method. The data were collected by observation, interview, and documentation techniques.  The results of this research showed that moral built through the program were about emotional management, mentoring, Muslimah sharing, leadership, mental building for the homeless children, Ramadan week, Da'wah Dai'at, and social media. The programs are divided into daily program, weekly program, and monthly program. Moral development process consists of two processes. Those are General process for all of the students; and specialized process for members of the organization. The evaluation of moral development was done by non-test technique or observation. The effect of this program is the students have good moral value and personality.